IMPLEMENTASI SISTEM INFORMASI PENDUKUNG AKREDITASI BERBASIS WEB PADA PRODI TEKNOLOGI INFORMASI UIN AR-RANIRY - Hendri Ahmadian; Ima Dwitawati; Malahayati Malahayati (UIN Ar-Raniry, 2019)
The supporting documents for accreditation forms are the most important part in the accreditation submission process. Otherwise the process of finding and collecting documents supporting accreditation forms are still done manually. This study aims to design the information systems which supports web-based accreditation in Department of Information Technology UIN Ar-Raniry. The designing process refered to regulation of National Accreditation Board for Higher Education and followed the latest instrument in 4.0 version. The application has namely SIDASI 4.0. The research method of this study is the Rapid Application Development (RAD) process which uses the PHP programming language and MYSQL as database engine. SIDASI 4.0 can only be accessed by users who have already registered and obtained an account as username and password. The SIDASI 4.0 have support the accreditation submission phase as the digital documentation forms.